Aircraft Position Estimation Comparison of Multilateration System Lateration Algorithms with Different Reference Selection Techniques (ELEKTRIKA- Journal of Electrical Engineering, 2019)
The lateration algorithm is used by the multilateration (MLAT) system to estimation the position of an aircraft using a time difference of arrival (TDOA) measurement vector generated from its transponder emissions detected at spatially deployed ground station (GS)s. The accuracy at which the aircraft position is determined by the lateration algorithm depends on several factors two of which are the choice and number of reference GSs used in generating the TDOA measurement vector. This paper compares the aircraft PE accuracy of a lateration algorithm using TDOA measurement vector generated using a single and double GS reference selection techniques which are respectively based on signal-to-noise (SNR) and condition number computations. The PE accuracy comparison is carried out at some selected aircraft positions with the GSs in a square configuration distribution. Monte Carlo (MC) simulation result shows that the PE error obtained by the lateration algorithm using TDOA measurement vector generated with the double GS reference selection technique is on the average 20% less than that obtained using the single GS reference selection technique.